PEMBELAJARAN PAI YANG INOVATIF - Mala Hayati Siahaan (Jurnal Al Wahyu, 2023)
Islamic Religious Education (PAI) uses an innovative approach to increase learning effectiveness. This research explores innovative strategies in PAI teaching, including the use of technology, active learning methods, and problem-based approaches. The focus is to identify the positive impact of this innovation on understanding religious concepts, active student participation, and the development of moral values. The research results show that innovative PAI learning can provide a deeper learning experience and increase student involvement in understanding religious values. The implications of these findings provide a basis for the development of PAI learning models that are more dynamic and relevant in facing modern-day challenges.